Scaling-up filariasis lymphoedema management into the primary health care system in Kerala State, Southern India: a case study in healthcare equity - Suma T. Krishnasastry; Charles D. Mackenzie; Rajeev Sadanandan (BMC, 2022)
Abstract Background Lymphatic filariasis (LF) remains one of the world's most debilitating parasitic infections and is a major contributor to poor health in many endemic countries. The provision of continuing care for all those affected by LF and its consequences is an important component of the United Nations' Sustainable Development Goals. The aim of this study is to integrate lymphedema care into the primary health care system of the State by developing lymphedema clinics at each district, through training of health personnel to fulfill WHO recommendation for morbidity management and disability prevention. Methods Selected health care providers from all the districts in Kerala State of India participated in intensive training sessions endorsed by the State's health administration. The six training sessions (from 5 June 2017 to 25 May 2018) included appropriate self-care information and development of individual plans for each participating institution to provide instruction and care for their lymphoedema patients. The learning achieved by attendees was assessed by pre- and post-training tests. The number of lymphoedema patients receiving care and instruction from the post-training activities of each participating institution was assessed from local records, 6 months after the conclusion of the training sessions. Results One hundred and eighty-four medical personnel (91 doctors and 93 nurses) from 82 medical institutions were trained which quickly led to the establishment of active lymphoedema clinics providing the essential package of care (EPC) for lymphoedema patients at all the participating institutions. Six months after the training sessions the number of previously unidentified lymphoedema patients registered and receiving care at these clinics ranged from 296 to almost 400 per clinic, with a total of 3,477 new patients receiving training in EPC. Conclusions Generalist health personnel, when appropriately trained, can provide quality lymphoedema care in public health settings and patients when provided services close to their home, are willing to access them. This is a feasible strategy for integrating long term care for LF patients into the national health system, and is a clear example of moving towards equity in health care for the medically underserved, and thus successfully addresses a major goal of the global program to eliminate lymphatic filariasis. Graphical Abstract